Evaluation of third treatment week as temporal window for assessing responsiveness on repeated FDG-PET-CT scans in Non-Small Cell Lung Cancer patients. (February 2018) - Lazzeroni, M.; Uhrdin, J.; Carvalho, S.; van Elmpt, W.; Lambin, P.; Dasu, A.; Wersäll, P.; Toma-Dasu, I.
Highlights: Predictive power of repeated PET images for NSCLC overall survival was investigated. PET images were acquired before treatment and during the third week. SUV values and their changes poorly correlate with overall survival. Quantities related to effective radiosensitivity were not predictive of survival. The third week of treatment might not be suitable for tumour response assessment. Abstract: Purpose: Early assessment of tumour response to treatment with repeated FDG-PET-CT imaging has potential for treatment adaptation but it is unclear what the optimal time window for this evaluation is. Previous studies indicate that changes in SUVmean and the effective radiosensitivity ( αeff, accounting for uptake variations and accumulated dose until the second FDG-PET-CT scan) are predictive of 2-year overall survival (OS) when imaging is performed before radiotherapy and during the second week. This study aims to investigate if multiple FDG-PET-derived quantities determined during the third treatment week have stronger predictive power. Methods: Twenty-eight lung cancer patients were imaged with FDG-PET-CT before radiotherapy (PET1) and during the third week (PET2). SUVmean, SUVmax, SUVpeak, MTV41%–50% (Metabolic Tumour Volume), TLG41%–50% (Total Lesion Glycolysis) in PET1 and PET2 and their change (), as well as average αeff ( α ¯ eff ) and the negative fraction of αeff values ( f α eff < 0 ) were determined. Correlations were sought between FDG-PET-derived quantities and OS with ROC analysis. Results: Neither SUVmean, SUVmax, SUVpeak in PET1 and PET2 (AUC = 0.5–0.6), nor their changes (AUC = 0.5–0.6) were significant for outcome prediction purposes. Lack of correlation with OS was also found for α ¯ eff (AUC = 0.5) and f α eff < 0 (AUC = 0.5). Threshold-based quantities (MTV41%–50%, TLG41%–50%) and their changes had AUC = 0.5–0.7. P-values were in all cases ≫0.05. Conclusions: The poor OS predictive power of the quantities determined from repeated FDG-PET-CT images indicates that the third week of treatment might not be suitable for treatment response assessment. Comparatively, the second week during the treatment appears to be a better time window.